Physical activity in hospitalised older people: the feasibility and acceptability of a volunteer-led mobility intervention in the SoMoVe™ study. (30th September 2019) - Lim, Stephen; Ibrahim, Kinda; Dodds, Richard; Purkis, Annette; Baxter, Mark; Rogers, Anne; Sayer, Avan Aihie; Roberts, Helen C
Abstract: Objectives: to determine the feasibility and acceptability of a volunteer-led mobility intervention to improve activity levels of older inpatients. Design: pre-post mixed methods study. Setting: acute medical wards for older people. Participants: one hundred inpatients aged ≥70 years who were mobile prior to hospitalisation: 50 participants were recruited before and 50 after the intervention was established. Twenty-five participants (patients, nurses, therapists and volunteers) were interviewed to determine the acceptability of the intervention. Interventions: twice daily volunteer-led mobility and bedside exercises. Main outcome measures: the feasibility of delivering a volunteer-led mobility intervention, including the recruitment, training and retention of volunteers and the acceptability of the intervention to patients and healthcare professionals. Secondary outcome measures included objectively measured daily step count, length of stay, 30-day readmission and any adverse events. Results: seventeen volunteers were recruited, 16 completed training and 12 were retained. Fifty participants (mean age 86 years) received the intervention, with a median daily step count of 912 steps (interquartile range [IQR] 295–1824) compared to the baseline group ( n = 50, mean age 87 years) of 636 steps (IQR 298–1468). No adverse events were reported. The intervention was acceptable to patients and staff. Facilitating factors of the intervention included the social aspect of the intervention and perceived benefits by stakeholders. Barriers identified included the busy clinical environment and lack of awareness of the intervention among staff. Conclusions: it was feasible to deliver a volunteer-led mobility intervention including the recruitment, training and retention of volunteers. The intervention was safe and acceptable to healthcare professionals and patients.